Pengembangan dan Implementasi Sistem Informasi Tiga Tema Pada Kemen-LHK - Roy Mubarak; Winny Purbaratri (Jurnal Ilmiah FIFO, 2022)
The integrated information system solution is one example of a solution from information technology which is currently very helpful for humans in processing data and presenting a report that is precise, fast and accurate. One example of a much-needed information system is the forest area management information system managed by the Ministry of Environment and Forestry. The information system is managed by the Directorate General, there are a number of systems that can be used to build a system used in management, supervision and control, namely an information system related to areas, deforestation and licensing, including the management of environmental permits through Amdal.net. This research was conducted with a two-method approach, namely a field study conducted by direct analysis of the system that is currently running where the system will later be integrated into a three-theme information system and literature study. which is done by collecting informationrelated to the forest area management system including Amdal.net. The result of the research is the application of the Three Themes Information System which is an integration of: Forest Area, Licensing and Deforestation Themes. The Ministry of Environment and Forestry can benefit from this three-themed system, namely the integration of mapping of several forest areas that is integrated with permits and deforestation. This web-basedsystem was built using the PHP 7.4 programming language with the Code Igniter framework and the MariaDB database.